“Make Sense Of It!”: The Role Of Mediation And Perceived Benefit In An Online Learning Environment - Ignasius Heri Satrya Wangsa (Konsumen & Konsumsi : Jurnal Manajemen, 2022)
The use of online learning platforms has significantly influenced critical understanding on the role of mediation and perceived-benefit. Those who are involved in an online learning environment have to expend effort to make sense of their virtual interaction. The goal in any online learning environment is to achieve authentic interaction. This conceptual research proposes two pillars in the rationalisation of virtual interaction. First, the existence of mediation should be based on its function as a medium to trigger active participation. Within this perspective the concept of involvement is explored. Second, there should be a mechanism to develop perceived-benefit orientation through which all parties involved in the interaction can achieve collective agreement, i.e. they can satisfy their own interests. Some practical implications are also discussed.